Isolation of Lycopene Component from Tamarillo (Solanum betaceum) - Damayanti, Jeanne Dewi; Azmilia, Ririn; Ainun, Zul; Amin R., Nur; Nurdin, M. Ilham (Indonesian Journal of Chemical Research, 2021)
Lycopene is a red pigment found in tamarillo with its function as an antioxidant that protects body cells from the negative effects of free radicals so that they do not trigger diseases, especially cancer and premature aging. This study was intended to improve the quality of tamarillo by isolating lycopene from tamarillo through an extraction process with chloroform as a solvent by maceration for 3 days at room temperature. The lycopene extract obtained was dissolved by means of a rotary evaporator at 40 oC under vacuum pressure and oven temperature at 60 oC. The lycopene obtained was analyzed by Gas Chromatography-Mass Spectrometry and the crystal structure of lycopene was characterized by Fourier Transform Infra-Red Spectroscopy. GCMS results showed that 0.21 g of lycopene was successfully isolated from 100 g of dried red tamarillo fruit powder. Functional group analysis using FT-IR at a wavelength of 978.23 cm-1 showed the R-CH=CH-R group; the -CH3- group of 1371.43 cm-1; the 1460.16 cm-1 indicates the bending vibration of -CH2-; the C=C chain of 1656.91 and 1745.64 cm-1; and the C-H of 2856.67 and 2926.11 cm-1 of the lycopene chain.